Strengthening community health supply chain performance through an integrated approach: Using mHealth technology and multilevel teams in Malawi - Mildred Shieshia; Megan Noel; Sarah Andersson; Barbara Felling; Soumya Alva; Smisha Agarwal; Amnesty Lefevre; Amos Misomali; Boniface Chimphanga; Humphreys Nsona; Yasmin Chandani (Edinburgh University Global Health Society, 2014)
, , In 2010, 7.6 million children under five died globally - largely due to preventable diseases. Majority of these deaths occurred in sub-Saharan Africa. As a strategy to reduce child mortality, the Government of Malawi, in 2008, initiated integrated community case management allowing health surveillance assistants (HSAs) to treat sick children in communities. Malawi however, faces health infrastructure challenges, including weak supply chain systems leading to low product availability. A baseline assessment conducted in 2010 identified data visibility, transport and motivation of HSAs as challenges to continuous product availability. The project designed a mHealth tool as part of two interventions to address these challenges.